Respiratory sinus arrhythmia as a potential measure in substance use treatment-outcome studies - Price, Cynthia J. (Addiction, 2016)
BACKGROUND AND AIMS: Dysfunction of physiological regulation systems may underlie the disrupted emotional and self-regulatory processes among people with substance use disorder (SUD). This paper reviews evidence as to whether respiratory sinus arrhythmia (RSA), as a psychophysiological index of emotional regulation, could provide useful information in treatment-outcome research to provide insights into recovery processes. METHODS: We reviewed use of RSA in clinical research and studies on SUD treatment. Search terms for the review of RSA in clinical research included respiratory sinus arrhythmia, heart rate variability, vagal, cardiac vagal control, psychophysiology, intervention, treatment, mindfulness, mind-body, mental health, substance use, chemical dependence, regulation, emotion regulation. For the review of RSA in intervention studies, we included only those that provided adequate description of psychophysiological methods, and examined RSA in the context of an intervention study. RESULTS: RSA appears to be able to provide an index of self-regulatory capacity; however it has been little used in either intervention or treatment research. Of the four intervention studies included in this review, all were mindfulness-based interventions. Two studies were with substance using samples and both showed pre-post increases in RSA and related improved substance use outcomes. Two of the three studies were RCTs and both showed significant increases in RSA in the experimental compared to comparison condition. CONCLUSION: Respiratory sinus arrhythmia may be a useful index of emotional regulation in people with substance use disorder, and a potential measure of underlying mechanisms for SUD treatment studies, particularly mindfulness-based interventions.